The Effect of Capital and Licensing on The Productivity of Msmes with an Innovative and Proactive Mindset as A Mediating Variable: A Study on Msmes in Majalengka Regency - Muhammad Khoirul Umam (PT. Publikasiku Academic Solution, 2025)
An entrepreneurial mindset influences how effective MSMEs are in facing various business challenges, such as capital and licensing. Apart from that, research on mindset factors in the context of MSMEs in Majalengka can produce new ideas that are more interesting and useful in formulating policies to accelerate the growth of MSMEs. This research analyzes the influence of capital and licensing on the productivity of MSMEs in the Majalengka Regency by considering innovative and proactive mindsets as mediating variables. The quantitative method was implemented by collecting data from 100 MSME samples using a questionnaire. The analysis results show that capital and licensing have a significant direct impact on the productivity of SMEs, with 77.2% of the variation in productivity explained by these two variables. However, an innovative and proactive mindset does not mediate between capital, licensing, and productivity. These findings indicate that to improve productivity, MSMEs must focus on enhancing access to capital and simplifying the licensing process. Support from the government in reducing bureaucracy is also an important factor in the efforts to develop MSMEs in the region.